Multi-dimensional competition in local governments, performance pressures, and corporate green innovation in China - Lina Ma; Xueyu Xing; Najaf Iqbal (Journal of Applied Economics, 2024)
Based on the panel data of China's listed companies from 2009 to 2020, this paper examines the relationship between multi-dimensional competition among local governments and corporate green innovation. It also investigates the influencing mechanism of performance pressures in this relationship. The results show that (1) Government competition with different motives has heterogeneous effects on green innovation. Growth and fiscal competition negatively affect green innovation, while investment attraction and regulation competition significantly positively affect green innovation. (2) The performance pressure significantly reduces the negative effect of fiscal competition and enhances the positive effect of investment attraction and regulation competition. (3) The regional heterogeneity analysis shows that investment attraction competition positively affects green innovation in the eastern, central, and western regions. While the impact of growth and fiscal competition in the eastern region is insignificant, the former is significantly negative in the central and western regions.
Keywords: 330; green innovation; Local government; multi-dimensional competition; performance pressures